America, Brexit and the security of Europe - Rees, Wyn (SAGE, 2017)
The Obama administration played a surprisingly interventionist role in the UK referendum on membership of the European Union, arguing that a vote to leave would damage European security. Yet this article contends that US attitudes towards the EU as a security actor, and the part played within it by the UK, have been much more complex than the US has sought to portray. While it has spoken the language of partnership, it has acted as if the EU has been a problem for US policy. The UK was used as part of the mechanism for managing that problem. In doing so America contributed, albeit inadvertently, to the Brexit result. With the aid of contrasting theoretical perspectives from Realism and Institutionalism, this article explores how America’s security relationship with the UK has helped to engineer a security situation that the US wanted to avoid.